The impact of obesity on the development of certain cancers in patients with type 2 diabetes - T.S. Vatseba; L.K. Sokolova; M.D. Tronko; I.K. Churpiy; M.O. Vatseba; V.V. Derpak (Medičnì Perspektivi)
The aim of the study was to investigate the effect of obesity on the development of cancer of certain localizations in patients with type 2 diabetes mellitus (T2D) and to explain the association mechanisms of obesity in diabetes and cancer. The study included retrospective analysis of first time diagnosed cancer cases in patients with T2D in 2012-2016 in Ivano-Frankivsk region. Analysis of the data was carried out using Statistica 12.0 (StatSoft Inc., USA) program. The data are presented in the tables as M ± SD (M ± standard deviation). Differences between the studied parameters were determined using the ANOVA- test, taking into account the Bonferroni correction. The relationship between the studied data was evaluated using the criterion of chi-square with Yates correction (χ²). The odds ratio (OR), 95% confidence interval, the positive and negative predictive value were calculated to determine the association between two events. The differences were considered significant at p < 0.05. According to the results, 533 cases of the first time diagnosed cancer were detected in patients with T2D. It was found that obesity is inherent in women with breast, uterine, ovarian and colorectal cancer; for men with prostate cancer and with colorectal cancer. According to the criterion of χ², the effect of obesity on the incidence of breast cancer in women (x2=8.46; p<0.05), and prostate cancer (x2=7.02; p<0.05) and colorectal cancer (x2=7.94; p<0.05) in men was proven. OR revealed an increased risk of breast cancer in women [OR=2.06; 95% CI (1.28-3.29); p<0.05], and prostate cancer [OR=2.94; 95% CI (1.37-6.32); p<0.05] and colorectal cancer [OR=2.87; 95% CI (1.42-5.82); p<0.05] in men associated with obesity. Thus, among patients with T2D, obesity increases the risk of breast cancer in women, prostate cancer and colorectal cancer in men. The mechanisms of association of obesity and cancer in patients with T2D are hyperglycemia, hyperinsulinemia, cytokine imbalance, hyperestrogenism (in estrogen-dependent cancer), and intestinal dysbiosis (in colorectal cancer).